Transcriptome Analysis Reveals Unfolded Protein Response Was Induced During the Early Stage of Burkholderia pseudomallei Infection in A549 Cells - Rao, Chenglong; Mao, Chan; Xia, Yupei; Zhang, Meijuan; Hu, Zhiqiang; Yuan, Siqi; Yang, Wenbo; Yan, Jingmin; Deng, Ling; Cai, Xiaolian; Mao, Xuhu; Li, Qian; et al. (Frontiers in Genetics, 2020)
Burkholderia pseudomallei is a zoonotic pathogen that usually affects patients' lungs and causes serious melioidosis. The interaction of B. pseudomallei with its hosts is complex, and cellular response to B. pseudomallei infection in humans still remains to be elucidated. In this study, transcriptomic profiling of B. pseudomallei-infected human lung epithelial A549 cells at 6 hours post-infection (hpi) and 12 hpi was performed to characterize the cellular response dynamics during the early infected stage. Gene ontology (GO) and Kyoto Encyclopedia of Gene and Genome (KEGG) pathway analysis were performed by using the online databases DAVID 6.8 and KOBAS 3.0. Real-time quantitative PCR and western blot were used for validation experiments. Compared with the negative control group (NC), a set of 36 common genes varied over time with a cut-off level of 1.5-fold change and a P-value < 0.05 were identified. Bioinformatics analysis indicated that the PERK-mediated unfolded protein response (UPR) were enriched as the most noteworthy biological processe category, which it was enriched as a branch of UPR in the signaling pathway of protein processing in endoplasmic reticulum. Other categories, such as inflammatory responses, cell migration and apoptosis were also focused. The molecular chaperone Bip (GRP78), PERK, PERK sensor-dependent phosphorylation of eIF2α (p-eIF2α) and ATF4 were verified increasing over time during the early infection stage, suggesting B. pseudomallei infection activated the PERK-mediated unfolded protein response in A549 cells. Collectively, these results provide important initial insights into the intimate interaction between B. pseudomallei and lung epithelial cells, which can be further explored towards elucidation of the cellular mechanisms of B. pseudomallei infections in humans.